Uji Toksisitas Subkronis Kombinasi Ekstrak Kedelai dan Jati Belanda terhadap Hematologi Tikus Wistar - MEILINAH HIDAYAT; SIJANI PRAHASTUTI; ESTHEROLITA DEWI; DEWI SAFITRI; SITI FARAH; ANDREANUS A. SOEMARDJI (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Subchronic toxicity test is performed to evaluate the eff ect and monitor the toxicity eff ects of a compound. The use of combination of ethanol extract of Detam 1 soybean (EEDS) and Jati Belanda (EEJB) as an antiobesity therapy will be consumed for a long time, therefore this test need to be done. The purpose of this research is to know the subchronic toxic eff ect of the test material on Wistar rat hematology. The study was conducted in accordance with the toxicity test stipulated by the Food and Drug Supervisory Agency of Indonesia, on 120 Wistar rats (60 male, 60 females) for 90 days and 120 days (satellite). Rats were divided into 6 groups. Parameters measured were leukocyte, hemoglobin, MCH, MCHC, MCV, hematocrit, RBC, and platelets using the Hematology Analyzer with the principle of colorimetry. The results showed that the eff ect of the test material on all hematologic parameters was not diff erent from the control group (p <0.005), except for the leukocyte, MCH and platelet levels, but the results could be negligible. Conclusion: subcronic toxicity